Pecking Order Theory and Trade-Off Theory of Capital Structure: Evidence from Indonesian Stock Exchange - Culata, Priska Ralna Eunike; Gunarsih, Tri (Bina Nusantara University, 2012)
Numerous empirical studies in the finance field have tested many theories for firms’ capital structure. The pecking order theory and the trade-off theory of capital structure is among the most influential theories of firms’ capital structure. The trade-off theory predicts optimal capital structure, while the pecking order theory does not predict an optimal capital structure. According to pecking order theory, the order of financial sources used is the source of internal funds from profits, short-term securities, debt, preferred stock and common stock last. The main objective of this study is to econometrically test whether the listed companies in Indonesian Stock Exchange follow the pecking order theory or the trade-off theory. Samples in this study are public companies listed during 2009-2010. The research questions are tested by running regression models. The empirical result of this study shows that the pecking order theory is not supported, while the trade-off theory is supported. This suggests that the capital structure of listed companies in Indonesian Stock Exchange is financed based on optimal capital structure, not by the order financial resources.